Internalisasi Pendidikan Karakter Bagi Siswa Melalui Literasi Sastra (“Kumpulan Cerpen Parmin”) Karya Jujur Prananto - Sumarno; Dalman Dalman; Sri Widayati (Universitas Muhammadiyah Kotabumi, 2022)
The problem which is discussed in this research is the internalization of character education for students through literary literacy (Parmin’s Short story compilation) by Jujur Prananto. Therefore, the purpose of this research is to internalize the character education for students through literary literacy literacy (Parmin’s Short story compilation) by Jujur Prananto. Descriptive qualitative is used as a method in this research. The result showed that Parmin’s short story compilation can be used as one of discourse to internalize excellent character values for students.